2021
DOI: 10.3390/antibiotics10080904
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility of Staphylococcus Species Isolated in Raw Chicken Meat from Retail Stores

Abstract: The study was aimed at evaluating the presence of antibiotic-resistant Staphylococcus aureus in retailed raw chicken meat from retail stores intended for human consumption. The presence, characterization, and antibiotic susceptibility of S. aureus from 38 retail raw chicken meat samples was performed using a standard microbiological method involving mannitol salt agar (MSA) and Mueller-Hinton agar (MHA). All the samples were positive for Staphylococcus species, of which 34 (89.5%) were positive for S. aureus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…According to the results of the present study, all S. aureus strains showed resistance against ampicillin, similar to same as a study conducted in Nigeria (Awogbemi et al, 2018). The high tetracycline resistance determined in previous studies was similar to that found in the present study (Kraushaar et al, 2017;Lika et al, 2021). Additionally, high antimicrobial resistance rates were demonstrated against kanamycin 74.41% in accordance with the results obtained in South Africa (Mkize et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…According to the results of the present study, all S. aureus strains showed resistance against ampicillin, similar to same as a study conducted in Nigeria (Awogbemi et al, 2018). The high tetracycline resistance determined in previous studies was similar to that found in the present study (Kraushaar et al, 2017;Lika et al, 2021). Additionally, high antimicrobial resistance rates were demonstrated against kanamycin 74.41% in accordance with the results obtained in South Africa (Mkize et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…S. aureus strains may also be transmitted to humans through the food chain via the fecal-oral route [ 23 ]. Studies have shown a high prevalence of staphylococci in food, such as, cheese and meat [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…N = Number of expected samples; Z 1-a/2 = Standard normal variant at 5% type I error (P< 0.05); P = prevalence expected based on previous studies [1.3% (Bernier-Lachance et al, 2020), 9.89% (Baghbaderani et al, 2020), 13.9% (Abbasi et al, 2021), 20.5 (Li et al, 2019), 29.1% (Rortana et al, 2021), 35.4% (Tegegne et al, 2021), 66.67% (Savariraj et al, 2020), 89.5% (Lika et al, 2021)]; d = Complete precision or error (which is 5%). Thus, the expected size of the sample was ≥351.…”
Section: Sample Collectionmentioning
confidence: 99%